2006
DOI: 10.1093/hmg/ddl184
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenetic role of the deafness-related M34T mutation of Cx26

Abstract: Mutations in the GJB2 gene, which encodes the gap junction protein connexin26 (Cx26), are the major cause of genetic non-syndromic hearing loss. The role of the allelic variant M34T in causing hereditary deafness remains controversial. By combining genetic, clinical, biochemical, electrophysiological and structural modeling studies, we have re-assessed the pathogenetic role of the M34T mutation. Genetic and audiological data indicate that the majority of heterozygous carriers and all five compound heterozygote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(78 citation statements)
references
References 71 publications
6
71
0
1
Order By: Relevance
“…Since the M34T substitution of hCx26 was reported to be the cause of nonsyndromic hearing loss (11), the functional role of the position 34 has been studied, and it has been suggested that M34T leads to a constriction of the channel pore (12). In our work, it is conceivable that the plug in the pore is locked into place by the hCx26M34A mutation because the physical obstruction is consistent with the decreased permeability of the hCx26M34A mutation (13).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Since the M34T substitution of hCx26 was reported to be the cause of nonsyndromic hearing loss (11), the functional role of the position 34 has been studied, and it has been suggested that M34T leads to a constriction of the channel pore (12). In our work, it is conceivable that the plug in the pore is locked into place by the hCx26M34A mutation because the physical obstruction is consistent with the decreased permeability of the hCx26M34A mutation (13).…”
Section: Discussionsupporting
confidence: 52%
“…The hCx26M34A mutant is a single-site mutation at the same position as the hCx26M34T mutant, which can cause prelingual nonsyndromic hereditary deafness (11). Although not as well characterized as hCx26M34T (12), this single-point mutation of a Met to Ala decreases dye coupling in exogenously transfected HeLa cells and forms structures indistinguishable from wild-type gap junctions (13). We succeeded in making 2D crystals of the hCx26M34A suitable for cryoelectron crystallography.…”
mentioning
confidence: 99%
“…For example, the residual permeability of the Cx26 mutant F83L for monovalent ions such as K + is reported to be 72% of the wild-type (Bruzzone et al 2003) and that of M34T 11% of the wild-type (Bicego et al 2006). Furthermore, mutations such as 35delG, V37I, W77R, L90P, S113R, M163V, 167delT, and R184P result in a complete loss of function with residual conductivity≤1% of the wild-type values (Bicego et al 2006;Bruzzone et al 2003). Other mutations, such as V84L, although reducing the conductivity for metabolites (Beltramello et al 2005), were not considered here.…”
Section: Cx26 Mutations Reducing Intercellular Connectivity (35delg)mentioning
confidence: 99%
“…These are well documented as leading to deafness in human populations. Missense mutations such as M34T or R75W have a dominant negative effect on hearing (Rabionet et al 2000) and functional analysis of such mutations have identified reduced ionic conductivity of the gap junction (GJ) as the associated defect (Bicego et al 2006;Bruzzone et al 2003). It has also been proposed that mutations such as V84L, with reduced permeability to metabolites such as IP 3 (Beltramello et al 2005) may exert their effect by interfering with the development and maintenance of the organ of Corti.…”
Section: Introductionmentioning
confidence: 99%
“…Another GJB2 mutation, M34T, found in a child with bilateral moderate to severe hearing loss, was thought to be a polymorphism (9). However, a recent study suggested that it could be pathologic even in the heterozygous state (18). The G160S mutation has been described by others as a polymorphism (19,20).…”
Section: Resultsmentioning
confidence: 99%